2002
DOI: 10.1002/sim.1253
|View full text |Cite
|
Sign up to set email alerts
|

Assessing intrarater, interrater and test–retest reliability of continuous measurements

Abstract: In this paper we review the problem of defining and estimating intrarater, interrater and test-retest reliability of continuous measurements. We argue that the usual notion of product-moment correlation is well adapted in a test-retest situation, whereas the concept of intraclass correlation should be used for intrarater and interrater reliability. The key difference between these two approaches is the treatment of systematic error, which is often due to a learning effect for test-retest data. We also consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
246
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(258 citation statements)
references
References 14 publications
(11 reference statements)
2
246
1
5
Order By: Relevance
“…Thus, ROIs in a total of 26 structural scans were drawn (by TZR) for intrarater comparison. An intraclass correlation test (Rousson et al, 2002) on each ROI volume showed a mean r = 0.884 for all regions (range 0.615 to 0.916). The lowest values were for the bilateral temporopolar cortex, all other correlations exceeded 0.8.…”
Section: Structural Image Post-processingmentioning
confidence: 95%
“…Thus, ROIs in a total of 26 structural scans were drawn (by TZR) for intrarater comparison. An intraclass correlation test (Rousson et al, 2002) on each ROI volume showed a mean r = 0.884 for all regions (range 0.615 to 0.916). The lowest values were for the bilateral temporopolar cortex, all other correlations exceeded 0.8.…”
Section: Structural Image Post-processingmentioning
confidence: 95%
“…whether the resulting measurements of this test are reproducible among sessions. As it was reasonable to believe that no systematic error occurred, the intraclass correlation coefficient (ICC) was estimated to ensure test-retest reliability between sessions (Rousson et al, 2002) ICC may be defined as the percentage of variability in measurements explained by the subject effect thus the larger this percentage the better the reliability. An ICC larger than 0.75 indicates good to excellent reliability, an ICC included between 0.40 and 0.75 indicates fair to good reliability, and finally an ICC lower than 0.40 indicates poor reliability (Corriveau et al, 2000).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Thus, ROIs in a total of 26 structural scans were drawn for intrarater comparison. An intraclass correlation test (Rousson et al, 2002) on each ROI volume showed a mean r ϭ 0.884 for all regions (range 0.615-0.916). The lowest values were for the bilateral temporopolar cortex, all other correlations exceeded 0.8.…”
Section: Regions Of Interestmentioning
confidence: 96%